ANALISIS PEMAHAMAN KONSEP FISIKA SISWA MELALUI KUNJUNGAN BELAJAR DARI RUMAH DI MASA PANDEMI COVID-19 - Aulia Safitri , Firda Yanti; Gustina (Universitas Tadulako, 2021)
This research is a qualitative descriptive study with the purpose of describing the understanding of physics concepts through study from home visits during the Covid-19 pandemic and knowing the factors that influence students' understanding of physics concepts. The subjects of this study were class VIII students of SMP Negeri 3 Dampelas who collected 10 students and selected 6 students through purposive sampling technique as respondents to be analyzed and interviewed, each of which 2 students were categorized as high, medium and low. The research instrument used in testing the understanding of physics concepts which includes 3 questions about simple aircraft material, knowledge to determine the factors that influence understanding of physics concepts and interview guidelines to confirm the statement of answers to the physics concept understanding test. The results of the study of the three physics concept indicators obtained an average percentage for the translation indicator (Translation) of 76,0% with a good interpretation, the assessment indicator (Interpretation) of 82,0% with a very good interpretation and the extrapolation indicator (Extrapolation) of 82,0% with a very good interpretation. From the three indicators of concept understanding, it can be said that the level of understanding of physical concepts has a good level of understanding. While the results of the questionnaire analysis to determine the factors that influence the understanding of physics concepts for class VIII students of SMP Negeri 3 Dampelas, namely internal factors including learning motivation of 70,0% are in the sufficient category, study habits of 72.5% are in the good category and student psychology of 72.5% are in the good category. External factors include the learning model of 71.2% in the sufficient category, 79.2% of school facilities and infrastructure in the very good category, the family environment of 69,0 % in the poor category and the community environment of 70.6% being in the sufficient category. So it can be said that these factors are sufficient to influence students' understanding of physics concepts through study from home visits during the Covid-19 pandemic.